The use of scoring rubrics in assessing ESL learners' writing performance: a review of literature - Rahmat, Nurhazlini; Mohamed Razali, Abu Bakar (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Writing demands learners’ knowledge and language skills. In the classroom setting, learners are exposed to the art of writing and their performance is measured. This is when teachers use scoring rubrics to evaluate their students’ performance on whether the writing product meets the requirements underlined in the scoring rubric. This paper attempts to highlight relevant literature pertaining to the use of rubrics in measuring ESL learners’ writing performance. The review was done on the basis of content analysis where the relevant data from the selected literature were analysed and the findings were reported based on three segments which are the interpretation and authenticity of scoring, the benefits of scoring rubrics in assessing students’ performance, and the impacts of scoring rubric to teachers’ instruction and students’ learning.